Stress level and emotional eating in obese and non-obese adolescents - Hajar Surya Wardani; Sapja Sapja Anatayu; Ratih Puspita Febrinasari (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The association between stress factors and emotional eating can contribute to the development of obesity. Boredom, stress, anxiety, and depression can lead to emotional eating, which involves the consumption of food to cope with negative emotions. Emotional eating often involves the consumption of high-calorie, comfortable foods that can contribute to weight gain. This study aimed to analyze the differences in stress levels and emotional eating between obese and non-obese adolescents. This research was conducted in May 2023 using an observational case-control study comparing obese and non-obese adolescents in a special region of Yogyakarta. A total of 139 respondents who attended this study were selected using multistage random sampling. Stress levels were measured using the Perceived Stress Scale-10 (PSS-10) questionnaire and emotional eating was assessed using the Emotional Eater Questionnaire (EEQ). Data were collected and analyzed using the Mann-Whitney test. Results: Most respondents had high stress levels (49,6%) and low emotional eaters (43,9%). There were differences in stress levels (p=0,004) and emotional eating (p=0,000) between the obese and non-obese adolescents. Conclusions, stress levels and emotional eating were different in obese and non-obese adolescents.